Ilmastodiskurssi Venäjän arktisella alueella - Yagodin, Dmitry (Idäntutkimus, 2021)
This study uses the case of the 2016 anthrax outbreak on the Yamal peninsula in north-western Siberia to discuss whether and how the incident could challenge the dominant discourse in Russia that neglects the problem of climate change – a potential cause of the outbreak. The study draws on a small sample of media materials that linked the incident to climate change on the national and regional levels. The analysis follows the premises of poststructuralist discourse theory and the concepts of dislocation and discursive logics to unpack the intricate relationships between the issues of economic development and environmental change in a region that is at once central to Russia’s fossil fuel economy and most vulnerable to the effects of climate change. The results point to the obstacles and opportunities for climate justice discourse in this context. Peer reviewed